Uji Aktivitas Antioksidan Kombinasi Daun Kopi Arabika (Coffea arabica) dan Daun Pandan (Pandanus amaryllifolius) dengan Metode DPPH - Retnaningtyas, Yuni; Hamzah, Muhammad Hafidi; Kristiningrum, Nia (Jurnal Farmasi Indonesia, 2017)
ABSTRACT : Antioxidants are nutrient that can prevent the oxidative damage in the body. Arabica coffee and pandan is most common species of plant found in Indonesia. Arabica coffee and pandan known as plants with antioxidant activity. This study aimed to determine and compare antioxidant activity of water and ether fraction from methanolic extract of Arabica coffee leaves, pandan leaves and both combination by DPPH method. Vitamin C was used as positive control. The result show that Arabica coffee leaves have antioxidant activity better than pandan leaves and also gives big donation of antioxidant activity in their combinations. Statistical analysis showed that antioxidant activity from all sample were significanly different (p<0,05).Â Â